Sceptyczna postawa Leszka Kołakowskiego wobec filozofii chrześcijańskiej - Turoń-Kowalska, Agnieszka (Folia Philosophica, 2018)
The paper presents Leszek Kołakowski’s attitude to Christian philosophy. Very often it is seen as informed by scepticism in the sense of some negative vigilance against dogmas and non-scientific contents. An important element of Kołakowski’s biography is his initial fascination with post-war socialism and subsequent “Hegelian bite”, which manifested in harsh criticism of Polish Catholicism. After the change of his views and compulsory emigration he kept researching religious attitude and religion itself. The paper concerns his views in this matter with exclusion of his “ideological” analyses. It consists of, first of all, Kołakowski’s attitude to transcendence-existence relation of medieval and modern order including the question of evil manifesting itself in the world as conceived in Christian philosophy. It also aims to give answer to the question of what form should Christianity take in the face of scientific concepts of world and man’s place within it. It deals also with Kołakowski’s attempt to define religion in the context of epistemological separation of the act of faith from intellectual cognition. According to him, religion should not pretend to attain a scientific level, which however does not negate its meaning for man.